Isolasi Bakteri Selulolitik Pada Ayam Kampung (Gallus gallus domesticus) Sebagai Kandidat Probiotik Ternak Unggas - Aidil Fitriyan Fadjar Suryadi, Muh. (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
This study aims to isolate cellulolytic bacteria derived from local chickens (Gallus gallus domesticus) and evaluate their potential in degrading cellulose in test media (CMC). Isolation was performed from the gastrointestinal tract of local chickens, which is expected to contain microorganisms with cellulose-degrading capabilities. The results of this study showed that the isolated bacteria can effectively break down cellulose, indicating their potential as probiotics that can help improve digestive health in poultry. Cellulolytic activity was tested by measuring the clear zone formed on agar media containing cellulose. The U5 bacterial isolate exhibited the highest ability to degrade cellulose substrate on agar media, marked by a clear zone of 35 mm, followed by U3 with a zone size of 33 mm. The formation of a clear zone on the CMC test medium indicates the presence of probiotic bacterial candidates, which need to be further tested for their biochemical characteristics to determine the biochemical properties of each bacterial candidate.